CO2 reforming of CH4 on mesoporous alumina‑supported cobalt catalyst: optimization of lanthana promoter loading - Tran, Ngoc Thang; P. Senthil, Kumar; Le, Quyet Van; Cuong, Nguyen Van; Phuong, Pham T. T.; A. A., Jalil; Sharma, Gaurav; Kumar, Amit; Sharma, Ajit; Ayodele, Bamidele Victor; Sumaiya, Zainal Abidin; Vo, Dai‑Viet N (Springer Nature, 2021)
The impact of La2O3 promoter loading on alumina-supported cobalt catalysts was investigated in terms of physicochemical properties and catalytic performance for CO2 reforming of methane (CRM) at stoichiometric CH4/CO2 ratio and 1023 K. Both Co3O4 (with crystal size: 5.2–8.4 nm) and La2O3 nanoparticles were finely dispersed on support surface. The promotional La2O3 effect could noticeably increase CH4 and CO2 conversions to 29.3% and 17.3%, correspondingly due to improved basic site concentration and decreasing crystallite size of active metal in association with promoter addition. 5%La loading was an optimal promoter content for reactant conversions as well as yield of H2 and CO. 5%La-10%Co/Al2O3 also exhibited the highest resistance to carbon deposition owing to the basic nature, redox feature and oxygen vacancy of La2O3 dopant. Notably, the H2/CO ratio obtained within 0.84–0.98 is preferable for Fischer-Tropsch reaction in downstream to yield liquid hydrocarbon fuels.